Comparative evaluation of topical Sodium fusidate cream in common pyodermas with topical gentamicin ointment and systemic antibiotics - Roy AK; Ghosh SK; Ganguly U; Basak S; Banatwalla KS; Basu S (Wolters Kluwer Medknow Publications, 1996)
ABSTRACT: One hundred cases of common pyodermas consisting of four groups, namely impetigo, furunculosis and chronic folliculitis were taken. Each group containing twenty five cases were divided again into three subgroups. From each group, 15 were treated with 2 percent Sodium fusidate cream, 5 were with 0.1 percent Gentamycin sulphate cream and the rest 5 with systemic Erythromycin stearate. In the group of Impetigo, Bockhart′s Impetigo and Furunculosis, topical Sodium fusidate cream showed excellent result, better than Gentamycin topical and equal to that of systemic Erythromycin stearate.